Quintana Roo Archaeology - Mathews, Jennifer P., 1969-; Shaw, Justine M., 1971- (Book collections on Project MUSE., 2005)
"The first volume devoted to the archaeology of Quintana Roo, this book reveals a long tradition of exploration and discovery in the region and an increasingly rich recent history of study. Covering a time span from the Formative period through the early twentieth century, it offers a sampling of recent and ongoing research by Mexican, North American, and European archaeologists." "Each of the chapters helps to integrate sites within and beyond the borders of the modern state, inviting readers to consider Quintana Roo as part of an interacting Maya world whose boundaries were entirely different from today's."--Jacket.